2004
DOI: 10.1073/pnas.0307348101
|View full text |Cite
|
Sign up to set email alerts
|

Impaired IgA class switching in APRIL-deficient mice

Abstract: The tumor necrosis factor (TNF) family member APRIL binds to the receptors BCMA on B cells and TACI on B and T cells. To investigate the role of APRIL in immunity, we generated APRIL-deficient mice. APRIL ؊/؊ mice have normal T and B lymphocyte development, normal T and B cell proliferation in vitro, but increased numbers of CD44 hi CD62L lo CD4 ؉ effector͞memory T cells and increased IgG responses to T-dependent antigens. Serum IgA levels were significantly decreased, and serum IgA antibody responses to mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
320
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(343 citation statements)
references
References 44 publications
16
320
1
6
Order By: Relevance
“…One strain of APRIL-deficient mice had lowered IgA serum levels and impaired mucosal IgA responses 21 that were not observed in a second APRIL-deficient strain. 22 Reduced IgA serum levels are also characteristic of TACI-deficient mice, indicating that APRIL might mediate IgA class switch, or survival of switched IgAsecreting cells, through TACI.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…One strain of APRIL-deficient mice had lowered IgA serum levels and impaired mucosal IgA responses 21 that were not observed in a second APRIL-deficient strain. 22 Reduced IgA serum levels are also characteristic of TACI-deficient mice, indicating that APRIL might mediate IgA class switch, or survival of switched IgAsecreting cells, through TACI.…”
Section: Introductionmentioning
confidence: 80%
“…21 IgM production in supernatants of B splenocytes cultured for 6 days was increased 3-and 6-fold in response to cross-linked APRIL and BAFF 60-mer, respectively, an effect that was mainly mediated by TACI ( Figure 4A). In contrast, BAFF 3-mer only induced a modest, BAFF-R-dependent response.…”
Section: Increased Immunoglobulin Production By B Splenocytes and Plamentioning
confidence: 99%
“…These negative association studies include candidate genes such as APRIL, where the corresponding mouse knock out shows impaired IgA class switching [43], and the BAFFR, where the initial study suggested an association with CVID in a German family [44]. The association of unusual PID case presentations in patients carrying the CD45 C77G polymorphism in a heterozygous form is intriguing [45].…”
Section: Negative Association Studies In Igad/cvidmentioning
confidence: 99%
“…Interestingly, APRIL is known to increase IgA and IgM but not IgG responses to T cell-dependent antigens (Stein et al, 2002). More specifically, APRIL is known to exclusively influence IgA isotype regulation: IgA production increases in APRIL transgenic mice (Stein et al, 2002), and conversely, IgA class switching recombination is impaired in APRIL-deficient mice (Castigli et al, 2004).…”
Section: Introductionmentioning
confidence: 99%